(2,6-Diisopropylphenyl)(2-thienylmethylene)amine - Imhof, Wolfgang (International Union of Crystallography, 2009)
The title compound, C(17)H(21)NS, was prepared by the condensation of thiophene-2-carbaldehyde with 2,6-diisopropylaniline. It crystallizes with two molecules in the asymmetric unit. The molecules are interconnected via a C—H⋯N hydrogen bond. The dihedral angles between the thiophene and phenyl rings are 81.7 (7) and 85.5 (7)°.